Paz, violencias y memoria histórica: tejiendo saberes para la construcción de la paz en la escuela. Unidad didáctica para la promoción de escenarios de paz en la escuela con estudiantes de grado 9 (2022)
The present thesis was developed to offer a robust and well-considered argumentation of the reasons, needs and difficulties that were involved in the construction of the didactic material called peace, violence, and historical memory: weaving knowledge for the construction of peace in the school, which would allow or enable the generation of spaces that would mark the construction of peace in the school. For this reason, throughout the following chapters it will be possible to find, one by one, the different elements and enunciations that made possible the creation of the didactic material, such as the formulations of the needs and difficulties of its consolidation, passing through a solvent explanation from the pedagogical referents on which it was built; until arriving, then, to the sections in which its elaboration, evaluation and the conclusions and recommendations arising from the evaluative process are made explicit